2015 IEEE 14th International Conference on Machine Learning and Applications (ICMLA) 2015
DOI: 10.1109/icmla.2015.199
|View full text |Cite
|
Sign up to set email alerts
|

Learning from Synthetic Data Using a Stacked Multichannel Autoencoder

Abstract: Abstract-Learning from synthetic data has many important and practical applications, An example of application is photosketch recognition. Using synthetic data is challenging due to the differences in feature distributions between synthetic and real data, a phenomenon we term synthetic gap. In this paper, we investigate and formalize a general framework -Stacked Multichannel Autoencoder (SMCAE) that enables bridging the synthetic gap and learning from synthetic data more efficiently. In particular, we show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 23 publications
0
36
0
Order By: Relevance
“…This behaviour could not be confirmed with our experiments. However, since our dataset is highly different from the dataset used in (Zhang et al, 2015), strong conclusions cannot be drawn.…”
Section: Testing Stepmentioning
confidence: 75%
See 3 more Smart Citations
“…This behaviour could not be confirmed with our experiments. However, since our dataset is highly different from the dataset used in (Zhang et al, 2015), strong conclusions cannot be drawn.…”
Section: Testing Stepmentioning
confidence: 75%
“…Although standard procedures to prevent overfitting have been used, overfitting seems to be responsible for the unsatisfying performance. In the work of Zhang et al (Zhang, et al, 2015), the SVM classifier performed better in roof type classification compared to a classifier based on a CNN only. This behaviour could not be confirmed with our experiments.…”
Section: Testing Stepmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that using such data for classifiers training is for the most part safe and will not result in worsening of classifier's accuracy. A practical method for learning image classifiers from synthetic data was presented by Zhang and others [13]. They identified a problem of distribution gap between real and synthetic data.…”
Section: Other Workmentioning
confidence: 99%